Alpha 1-adrenoceptor signalling contributes to toxic effects of catecholamine on electrical properties in cardiomyocytes. Issue 7 (19th January 2021) - Huang, Mengying; Fan, Xuehui; Yang, Zhen; Cyganek, Lukas; Li, Xin; Yuecel, Goekhan; Lan, Huan; Li, Yingrui; Wendel, Angela; Lang, Siegfried; Bieback, Karen; El-Battrawy, Ibrahim; et al.
Abstract: Aims: This study aimed to investigate possible roles and underlying mechanisms of alpha-adrenoceptor coupled signalling for the pathogenesis of Takotsubo syndrome (TTS). Methods and results: Human-induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) were treated with a toxic concentration of epinephrine (Epi, 0.5 mM for 1 h) to mimic the setting of TTS. Patch-clamp technique, polymerase chain reaction (PCR) and Fluorescence-activated cell sorting (FACS) were employed for the study. High concentration Epi suppressed the depolarization velocity, prolonged duration of action potentials and induced arrhythmic events in hiPSC-CMs. The Epi effects were attenuated by an alpha-adrenoceptor blocker (phentolamine), suggesting involvement of alpha-adrenoceptor signalling in arrhythmogenesis related to QT interval prolongation in the setting of TTS. An alpha 1-adrenoceptor agonist (phenylephrine) but not an alpha 2-adrenoceptor agonist (clonidine) mimicked Epi effects. Epi enhanced ROS production, which could be attenuated by the alpha- adrenoceptor blocker. Treatment of cells with H2 O2 (100 µM) mimicked the effects of Epi on action potentials and a reactive oxygen species (ROS)-blocker ( N -acetyl-I-cysteine, 1 mM) prevented the Epi effects, indicating that the ROS signalling is involved in the alpha-adrenoceptor actions. Nicotinamide adenine dinucleotide phosphate hydrogen (NADPH) oxidases were involved in alpha 1-adrenoceptor signalling. A protein kinase C (PKC) blocker suppressed the effects of Epi, phenylephrine and ROS as well, implying that PKC participated in alpha 1-adrenoceptor signalling and acted as a downstream factor of ROS. The abnormal action potentials resulted from alpha 1-adrenoceptor activation-induced dysfunctions of ion channels including the voltage-dependent Na + and L-type Ca 2+ channels. Conclusions: Alpha 1-adrenoceptor signalling plays important roles for arrhythmogenesis of TTS. Alpha-adrenoceptor blockers might be clinically helpful for treating arrhythmias in patients with TTS.